Improvement Teachers' Digital Literacy Ability Through Workshops on Application E-Learning Platforms in Distance Learning - Andriyani; Chairil Hikayat; Ahmad Asrori; Lalu Indar Anggara Putra; Muhammad Syakir Yahya Hairun; Yusuf Muri Salampessy (PT FORMOSA CENDEKIA GLOBAL, 2023)
This community empowerment program activity (Prodamat) aims to improve the digital literacy ability of teachers at MTs Al-Mu'min Muhammadiyah Tembarak through workshops on the use of e-learning platforms in Distance Learning (PJJ). The methods for implementing service activities consist of tests measuring teachers' digital literacy abilities, workshops introducing e-learning platforms, assistance in designing distance learning using e-learning platforms and evaluating the effectiveness of workshop activities on teachers' digital literacy abilities. The evaluation results show an increase in teachers' digital literacy ability after the workshop on the application of e-learning in distance learning. The improvement in teachers' digital literacy ability can be seen from the improvement in the intensity of the application and use of digital literacy in learning activities, the variety of digital-based reading materials and teaching aids, also the number of activities that use digital media